Societal acceptance of hydrogen for domestic and export applications in Australia. (5th August 2022) - Lozano, Lina Lopez; Bharadwaj, Bishal; de Sales, Alain; Kambo, Amrita; Ashworth, Peta
Abstract: With the urgent need to decarbonise the world's energy system, clean hydrogen is emerging as a potential technological solution. As with any new technology, understanding the public's response to hydrogen is critical to its success. Most studies examining public attitudes towards hydrogen have focused on refuelling stations and transport options. As a first of its kind, using a national survey (N = 2785) we evaluate the Australian public's response towards hydrogen for domestic and export use. In Australia, acceptance of hydrogen in domestic applications was influenced by its relative cost, ability to reduce air pollution and associated health benefits. Further, support for a hydrogen export industry was influenced by levels of trust in the government to manage the associated risks and the industry's commitment to climate protection. The paper concludes that effective, nuanced communication and engagement along with supporting financial policies will be critical in facilitating societal acceptance of hydrogen in Australia. Graphical abstract: Image 1 Highlights: An Australian national survey investigating subjective support for hydrogen. Technology Acceptance Framework variables strongly influence hydrogen support. The influence of TAF variables is observed in domestic use and hydrogen export. One third of participants support a hydrogen plant being built near them. Behavioural factors did not have a significant influence on hydrogen support.